Palmitoylated Proteins in Dendritic Spine Remodeling - Albanesi, Joseph P.; Barylko, Barbara; DeMartino, George N.; Jameson, David M. (Frontiers in Synaptic Neuroscience, 2020)
Activity-responsive changes in the actin cytoskeleton are required for the biogenesis, motility, and remodeling of dendritic spines. These changes are governed by proteins that regulate the polymerization, depolymerization, bundling, and branching of actin filaments. Thus, processes that have been extensively characterized in the context of non-neuronal cell shape change and migration are also critical for learning and memory. In this review we highlight actin regulatory proteins that associate, at least transiently, with the dendritic plasma membrane. All of these proteins have been shown, either in directed studies or in high- throughput screens, to undergo palmitoylation, a potentially reversible and stimulus-dependent cysteine modification. Palmitoylation increases the affinity of peripheral proteins for the membrane bilayer and contributes to their subcellular localization and recruitment to cholesterol-rich membrane microdomains.